2021
DOI: 10.3390/metabo11110796
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Death in Diabetes: Past Discoveries, Present Understanding, and Potential Future Advances

Abstract: β-cell death is regarded as a major event driving loss of insulin secretion and hyperglycemia in both type 1 and type 2 diabetes mellitus. In this review, we explore past, present, and potential future advances in our understanding of the mechanisms that promote β-cell death in diabetes, with a focus on the primary literature. We first review discoveries of insulin insufficiency, β-cell loss, and β-cell death in human diabetes. We discuss findings in humans and mouse models of diabetes related to autoimmune-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 283 publications
(389 reference statements)
2
17
0
1
Order By: Relevance
“…Although apoptosis is widely viewed as the principal mechanism of β-cell death in diabetes [ 56 , 57 ], necroptosis has recently been recognized as a form of programmed cell death that contributes to disease pathogenesis in disorders such as Alzheimer's disease and osteoarthritis [ [38] , [39] , [40] ]. Despite potential relevance to the islet inflammation and β-cell autoimmunity observed in T1D, however, non-apoptotic mechanisms of β-cell death have not been well studied [ [58] , [59] , [60] ]. Given our finding that β cells are susceptible to caspase-independent cell death, we evaluated the role of RIPK3 in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Although apoptosis is widely viewed as the principal mechanism of β-cell death in diabetes [ 56 , 57 ], necroptosis has recently been recognized as a form of programmed cell death that contributes to disease pathogenesis in disorders such as Alzheimer's disease and osteoarthritis [ [38] , [39] , [40] ]. Despite potential relevance to the islet inflammation and β-cell autoimmunity observed in T1D, however, non-apoptotic mechanisms of β-cell death have not been well studied [ [58] , [59] , [60] ]. Given our finding that β cells are susceptible to caspase-independent cell death, we evaluated the role of RIPK3 in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple studies have demonstrated the involvement of UPR in the development and progression of metabolic diseases (for a review, see [ 47 ]). Thus, nowadays, it is known that ER stress participates in the impairment of insulin secretion and action; furthermore, ER stress has also been related to the development of degenerative complications (for a review, see [ 48 , 49 , 50 ]).…”
Section: Endoplasmic Reticulum Stress (Er Stress) and Inflammation In Dmmentioning
confidence: 99%
“…It was demonstrated that the development of obesity was accompanied by increased production of inflammatory cytokines by the adipose tissue, defining obesity as a disease of a subclinical inflammatory activity [ 53 ]. Rapidly, it was verified that pro-inflammatory activity would be spread to other territories, participating in the pathogenesis of T2D [ 50 , 51 , 52 ].…”
Section: Endoplasmic Reticulum Stress (Er Stress) and Inflammation In Dmmentioning
confidence: 99%
“…It is well established that exposure of pancreatic islet beta cells to metabolic stress conditions (e.g., high glucose, saturated fatty acids, biologically active sphingolipids, and pro-inflammatory cytokines) results in significant alterations in cellular function, including induction of oxidative and endoplasmic reticulum (ER) stress, stress kinase activation, mitochondrial dysfunction, and nuclear collapse leading to cell demise [1][2][3][4][5][6][7][8][9][10]. Several underlying signaling pathways have been proposed, including induction of apoptotic genes, in the cascade of events leading to dysfunction of the islet beta cells under metabolic stress [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%